Baculovirus lef-12 Is Not Required for Viral Replication - Guarino, Linda A. (American Society for Microbiology, 2002)
The baculovirus lef-12 (orf41) gene is required for transient expression of baculovirus late genes. To analyze the role of LEF-12 in the context of infected cells, two mutant viruses were constructed. Both mutants were viable in Trichoplusia ni High 5 and Spodoptera frugiperda Sf9 cells. Single-step growth curves, however, indicated that virus yields were reduced approximately fivefold in the absence of LEF-12. Pulse-labeling of infected cells revealed that LEF-12 mutant viruses entered the late phase and synthesized late proteins at levels equivalent to or only twofold lower than those of wild-type virus-infected cells. Western blot analyses confirmed that LEF-12 was not synthesized in cells infected with mutant virus. In wild-type virus-infected cells, LEF-12 was not detected until 18 h postinfection, and accumulation of LEF-12 peaked at 24 to 36 h postinfection. Primer extension mapping revealed that lef-12 mRNA was synthesized by 12 h postinfection and peaked between 18 and 24 h postinfection. Furthermore, synthesis of lef-12 mRNA and LEF-12 protein were inhibited by the addition of aphidicolin, indicating that lef-12 is expressed after DNA replication.